Master in Sustainable Tropical Agriculture: Trasnforming Agriculture in Latin America - Sanders, Arie; Mclean, Francis Denisse; Murillo, José Óscar; Rosas, Juan Carlos (Zamorano: Escuela Agrícola Panamericana, 2024)
This document was prepared by Arie Sanders, Francis Denisse McLean, José Óscar Murillo, and Juan Carlos Rosas. The authors were part of the Master in Sustainable Tropical Agriculture and work for the Graduate Program of the Panamerican Agricultural School, Zamorano. The development, editing, and production of this document were made possible thanks to the support of the Nippon Foundation within the framework of the “Master’s Scholarship at Zamorano” project (Project ID 2017458430). The contents and opinions expressed herein are solely the authors’ responsibility and do not necessarily reflect the views of EAP Zamorano or the Nippon Foundation. The designations employed and the presentation of the material in this document do not imply the expression of any opinion whatsoever on the part of Zamorano and the Nippon Foundation concerning the legal or development status of any country, territory, city, or area or of its authorities, or concerning the delimitation of its frontiers or boundaries. The mention of specific companies or products of manufacturers, whether or not these have been patented, does not imply that Zamorano and the Nippon Foundation endorse or recommend them in preference to others of a similar nature that are not mentioned. This document generically uses masculine language to facilitate reading and comprehension. All references to individuals in the masculine gender should be understood as inclusive, encompassing all genders, with no intent of discrimination or exclusion. Zamorano is committed to promoting equality and inclusion in all its documents and communications.